Performance Comparison of MANET Routing Protocols - Ahmad, Ibrahim Ahmad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Mobile ad-hoc networks can be described as a broad topic in a networking field that faces many challenges and issues to secure the network surroundings. There are different types of routing protocols designed to meet different requirements in ad-hoc networks because of their unorganized nature. Network topology can change frequently depending on the availability, velocity, battery life and the number of nodes in these networks. Over the recent years, security issues in ad-hoc networks have seen a great deal of thought. The vast majority of investigation focuses on the exploration of specific explicit security zones, to make sure the routing protocols are well secured. This study mainly discusses reactive and proactive routing protocols designed for mobile ad-hoc networks and compares some of them with simulation results. Packet delivery ratio, end-to-end delay and throughput values for different simulation environments are analyzed in these simulations. In addition to this, security concerns and possible solutions in ad-hoc networks is also considered deeply.

ÖZ: Mobil geçici ağlar, ağ çevresini güvence altına almak için birçok zorluk ve sorunla karşı karşıya kalan, bilgisayar ağları alanında geniş bir konu olarak tanımlanabilir. Düzensiz yapıları nedeniyle geçici ağlarda farklı gereksinimleri karşılamak üzere tasarlanmış farklı türde yönlendirme protokolleri vardır. Ağ topolojisi, bu ağlardaki düğümlerin kullanılabilirliği, hızı ve pil ömrüne bağlı olarak sık sık değişebilir. Son yıllarda, geçici ağlardaki güvenlik sorunları üzerinde çokça düşünülmüştür. Araştırmaların büyük çoğunluğu, yönlendirme protokollerinin iyi bir şekilde güvence altına alındığından emin olmak için belirli açık güvenlik bölgelerinin araştırılmasına odaklanır. Bu çalışma esas olarak mobil geçici ağlar için tasarlanmış reaktif ve proaktif yönlendirme protokollerini tartışmakta ve bazılarını simülasyon sonuçlarıyla karşılaştırmaktadır. Bu simülasyonlarda farklı simülasyon ortamları için paket teslim oranı, uçtan uca gecikme ve verim değerleri analiz edilmektedir.
Master of Technology in Information Technology. Institute of Graduate Studies and Research. Thesis (M.Tech.) - Eastern Mediterranean University, School of Computing and Technology, 2021. Supervisor: Asst. Prof. Dr. Hüsnü Bayramoğlu.
Keywords: School of Computing and Technology; Computer security Computer networks--Security; Ad-hoc networks, routing protocols, reactive, proactive, delay, throughput, comparison, simulation